Pharmacological and non-pharmacological treatment approaches to chronic lumbar back pain - Ketenci, Ayşegül (Turkish journal of physical medicine and rehabilitation, 2021)
Low back pain is a common and important cause of disability. Chronic pain increases disability and cost. In this review, we discuss pharmacological and non-pharmacological treatment approaches for chronic low back pain in the light of current data and guidelines.